The Thermoregulatory and Thermal Responses of Individuals With a Spinal Cord Injury During Exercise, Acclimation and by Using Cooling Strategies–A Systematic Review - Grossmann, Fabian; Flueck, Joelle Leonie; Perret, Claudio; Meeusen, Romain; Roelands, Bart (Frontiers in Physiology, 2021)
Background: In individuals with a spinal cord injury thermoregulatory mechanisms are fully or partially interrupted. This could lead to exercise-induced hyperthermia in temperate conditions which can be even more distinct in hot conditions. Hyperthermia has been suggested to impair physiological mechanisms in athletes, which could negatively influence physical performance and subjective wellbeing or cause mild to severe health issues. Objective: The aim was to evaluate the literature on the thermoregulatory and thermal responses of individuals with a spinal cord injury during exercise in temperate and hot conditions taking the effects of cooling techniques and heat acclimation into account. Data sources: Two electronic databases, PubMed and Web of Science were searched. Studies were eligible if they observed the influence of exercise on various thermoregulatory parameters (e.g. core and skin temperature, sweat rate, thermal sensation) in individuals with a spinal cord injury. Results: In total 32 articles were included of which 26 were of strong, 3 of moderate and 3 of weak quality. Individuals with a high lesion level, especially those with a tetraplegia, reached a higher core and skin temperature with a lower sweat rate. The use of cooling techniques before and during exercise can positively affect the burden of the impaired thermoregulatory system in all individuals with a spinal cord injury. Conclusion: Due to the absence of normal thermoregulatory abilities, individuals with a high-level spinal cord injury need special attention when they are exercising in temperate and hot conditions to prevent them from potential heat related issues. The use of cooling techniques can reduce this risk.